EXPRESSIVE AND FORMATIVE ESSENCE OF HARMONIC VERTICAL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
This article analyzes the importance of expressive abilities and formative meanings of harmonic devices in the initial lessons of Harmony, on the need for methodological analysis and adaptation of their explanatory approaches to the learning process. This necessity arises from the fact that students are able to master science, to guide their artistic and creative imagination and performance. Special attention should be given to the variety of forms and methods of teaching during the course of Harmony. In this respect, the teacher should take into account and continuously analyze such processes as students' perception, thinking, perception and implementation.